Courting conflict : the Israeli military court system in the West Bank and Gaza - Hajjar, Lisa, 1961- (University of California Press, 2005)
Israel's military court system is the centrepiece of Israel's apparatus of control in the West Bank and Gaza. Since 1967 it has witnessed the prosecution of hundreds of thousands of Palestinians. Hajjar explores both Israeli & Palestinian perspectives on this institution.
Keywords: Military courts -- West Bank.; Military courts -- Gaza Strip.; War and emergency powers -- Israel.; Rule of law -- Israel.; Palestinian Arabs -- Civil rights.; Cours militaires -- Cisjordanie.; Cours militaires -- Gaza, Bande de.; Pouvoirs exceptionnels -- Israël.; Règle de droit -- Israël.; Palestiniens -- Droits.; LAW -- Military.; HISTORY -- Middle East -- General.; Military courts; Palestinian Arabs -- Civil rights; Rule of law; War and emergency powers; Gaza Strip; Israel; West Bank